Brain Edema XII 2003
DOI: 10.1007/978-3-7091-0651-8_91
|View full text |Cite
|
Sign up to set email alerts
|

Chronological changes of perihematomal edema of human intracerebral hematoma

Abstract: Recent investigations have indicated the importance of secondary brain damage in the pathophysiology of intracerebral hemorrhage (ICH), which includes ischemic brain damage and edema formation around a hematoma. The purpose of the current study is to investigate chronological changes of perihematomal edema in patients with human ICH and also the correlation between volume of perihematomal edema and neurological status. Fourteen patients with medium-sized putaminal hemorrhage (29.4 ± 13.2 ml) without hematoma e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 5 publications
4
81
0
2
Order By: Relevance
“…This finding is consistent with results obtained from previous observational studies suggesting that perihematomal edema develops within 3 hours after onset of ICH and peaks several, perhaps between 10 and 20, days later. 6,7,14,15 In cross-sectional analyses, there were highly significant correlations between hematoma and perihematomal edema volumes at baseline and at 24 and 72 hours. Longitudinal analyses demonstrated that the baseline variables that were independently associated with absolute growth of edema volumes were lower systolic BP and baseline hematoma volume, and those independently associated with relative growth of edema were history of hypertension, baseline hematoma volume, and earlier time from onset to CT. Of these variables, however, baseline hematoma volume was the only factor that independently predicted both absolute and relative growth of perihematomal edema.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with results obtained from previous observational studies suggesting that perihematomal edema develops within 3 hours after onset of ICH and peaks several, perhaps between 10 and 20, days later. 6,7,14,15 In cross-sectional analyses, there were highly significant correlations between hematoma and perihematomal edema volumes at baseline and at 24 and 72 hours. Longitudinal analyses demonstrated that the baseline variables that were independently associated with absolute growth of edema volumes were lower systolic BP and baseline hematoma volume, and those independently associated with relative growth of edema were history of hypertension, baseline hematoma volume, and earlier time from onset to CT. Of these variables, however, baseline hematoma volume was the only factor that independently predicted both absolute and relative growth of perihematomal edema.…”
Section: Discussionmentioning
confidence: 91%
“…5 Development of perihematomal edema also leads to an elevation in intracranial pressure or hydrocephalus with subsequent clinical deterioration. 6,7 There are several potential mechanisms underlying the formation of cerebral edema after ICH. 4 In a very early phase (first few hours) there is the development of hydrostatic pressure and clot *The INTERACT Investigators are listed in appendix e-1 on the Neurology ® Web site at www.neurology.org.…”
mentioning
confidence: 99%
“…Hemostasis is eventually achieved by activation of the coagulation cascade along with mechanical tamponade. 34 In rare occasions, surgical specimens are found to have areas of both hemorrhagic and ischemic foci (Fig. 1).…”
Section: Pathogenesis Of Caa and Related Hemorrhagesmentioning
confidence: 99%
“…Most hematoma enlargement occurs in the first hours following ictus, but this growth can extend for many hours [40,41] . Disruption of the blood-brain barrier implies in the formation of plasma-derived perihematomal edema [42] , which grows rapidly in the first two or three days and reaches full extension about fourteen days after ICH onset [43,44] . Edema evolution can be described in three phases [45] .…”
Section: Pathophysiologymentioning
confidence: 99%